The role of religion in economic and demographic behavior in the United States: a review of the recent literature - Evelyn Lilian Lehrer (Institute for the Study of Labor (IZA), 2008)
This paper presents a critical review and synthesis of recent research on the role of religion in economic and demographic behavior in the United States. Relationships reviewed include the effects of religion on investments in human capital, labor supply and wealth accumulation; union formation and dissolution; and fertility. The paper also comments on the growing literature on the implications of religious dissimilarity between the spouses; on two different, possibly countervailing ways in which religiosity may affect demographic and economic behavior; and on the importance of estimating models that allow for possible non-linearities in the effects of religiosity.
urn:nbn:de:101:1-20080619113
Keywords: J1; 330; Religion; marriage; divorce; education; fertility; female labor supply; Religion; Familienökonomik; Bildungsinvestition; Arbeitsangebot; Frauenerwerbstätigkeit; USA